Process modeling and optimization of titanium alloy Ti-6Al-7Nb during WEDM using regression and ANN - Sharma V.; Misra J.P.; Singhal S. (My University, 2025)
Titanium alloys became multifunctional materials; initially created for the aerospace industry, they now have numerous applications in engineering and the medical field. In the present study, “Ti-6Al-7Nb” titanium alloy is machined using wire electric discharge machining (WEDM). This study investigates the effects of controllable machining variables such as Spark on-time (Ton), Spark off-time (Toff), Servo Voltage (Sv), and Peak Current (Ip) on productivity as measured by material removal rate (MRR) and surface integrity. Current research seeks to conduct a wire-electric discharge processing feasibility analysis for Ti-6Al-7Nb, a titanium alloy free from the catatoxic element vanadium. The performance of a process is evaluated based on the MRR and surface topography. After performing 81 experiments based on the Full factorial design of 3k, mathematical modeling and ANOVA analysis were conducted. The regression model is formed with a correlation coefficient (R) 0.94, which is further improved using artificial neural network (ANN) modeling. The values predicted by the ANN model are in outstanding conformity with experimental findings. The correlation coefficient (R) value in this investigation is 0.9912, which is very close to 1. It is evident that the ANN model's prediction accuracy is high. Using scanning electron microscopy, the surface conditions of the machined surface are examined. In order to evaluate the postprocess effects, the tool wear characteristics and the formation of a white layer on the surface produced are analyzed. This study examines the formation of oxide layers, craters, spherical droplets, and microcracks on the processed surface at low- and high-energy conditions. Following a thorough analysis, the discovery was made that machined surfaces contain debris, fissures, craters, and spherical particles. Additionally, to determine the elemental composition of the surface, energy-dispersive X-ray spectroscopy analysis has been carried out. © IMechE 2023.